The perceptions of users on sense of place in urban heritage: street of harmony, Georgetown, Penang / Nur Faiza Husna Roslan and Nadiyanti Mat Nayan - Roslan, Nur Faiza Husna; Mat Nayan, Nadiyanti (2024)
Understanding 'sense of place' is key in revitalising cultural places since it symbolises a layering of histories, tangible history, and intangible heritage. This study examines the perceptions of local communities towards cultural heritage regarding sense of place in Urban Heritage Site: Street of Harmony, Georgetown, Penang Malaysia. A few surveys question was carried on with local communities, observations and digital photo analysis were also carried out. It is in the intricacies of intangible heritage practices and their authentic expression; the local communities feel attached to and claim ownership of the place. Understanding this and how it translates into the site's stewardship is critical in protecting its value, management, and ongoing revitalisation.